The Adoption of E-Auction in Indonesia: The Extended Technology Acceptance Model Study - Claudia Pricilia Chandra (iBuss Management, 2015)
In Indonesia, e-commerce generally associated with online shop. However, e-commerce’s scope is bigger than just online shops; there are various other business/transaction forms that existed. Electronic auction or e-auction is one of the major online transaction forms (Huang & Dai, 2006). Nevertheless, some e-auction companies that entered Indonesia is struggling to penetrate Indonesia market (Cosseboom, 2014). This present study focused on the impact of extended Technology Acceptance Model (TAM) constructs (trust, enjoyment, perceived ease of use, and perceived usefulness) (Davis, 1989; Pavlou, 2003; Childers et al., 2001) and the antecedent constructs (security, time consumption, economic gain, and playfulness) in shaping Indonesian Consumers’ attitude in the adoption of e-auction. To collect the data, simple random sampling method was employed. An online survey spread to the e-mail subscribers in an e-auction website, a total of 228 usable responses were obtained. Confirmatory Factor Analysis (CFA) used to assess the measurement model, Structural Equation Modeling (SEM) used to test the hypotheses. Result indicated that Security, Economic Gain, and Playfulness have significant positive impact to extended TAM constructs, while time Consumption has negative, but insignificant impact to extended TAM constructs. In addition, all extended TAM constructs have significant positive impact toward attitude in using e-auction. Keywords: E-Auction; Attitude; Confirmatory Factor Analysis; Structural Equation Modeling; and Technology Acceptance Model